Seerat of the Last Prophet Muhammad صلی اللہ علیہ وآلہ واصحابہ وسلم: For only Muslims or for the Whole Humanity - Dr. Syed Aftab Alam; Ammara Tanveer (MEI, 2023)
Muslims understand that they are superior to all followers of other religions due to believe that the Last Prophet Muhammad صلی اللہ علیہ وآلہ واصحابہ وسلم gave them the entire guidance for living the best lives of here and hereafter and common Muslims have view that they are the only addressee of the last prophet. The questions are generated that is superiority concern only for having the best guidance or it relates to act upon those guidance and are Muslims only addressee of the Last Prophet Muhammad صلی اللہ علیہ وآلہ واصحابہ وسلم? To answer these questions, an analytical study of Hadiths of the Last Prophet Muhammad صلی اللہ علیہ وآلہ واصحابہ وسلم was done and found that in about 90% of his sayings, the Last Prophet Muhammad صلی اللہ علیہ وآلہ واصحابہ وسلم addressed to the humanity with the terms i.e. آدمی،